Preoperative anemia management program reduces blood transfusion in elective cardiac surgical patients, improving outcomes and decreasing hospital length of stay. Issue 9 (15th July 2021) - Cahill, Christine M.; Alhasson, Bassam; Blumberg, Neil; Melvin, Amber; Knight, Peter; Gloff, Marjorie; Robinson, Renee; Akwaa, Frank; Refaai, Majed A.
Abstract: Background: Anemia is an independent risk factor for hospitalization, readmission, prolonged length of stay (LOS), diminished quality of life, and mortality. A multidisciplinary program was implemented to manage anemia preoperatively as a patient blood management (PBM) initiative. Methods and Materials: From March 2016 to August 2018, 240 patients were screened for anemia during their preoperative cardiovascular visit. About 52/240 (22%) were found to be anemic and met out inclusion criteria. Also, 45/52 (87%) had iron deficiency anemia and 7 (13%) had anemia without iron deficiency. A similar historical cohort of patients undergoing elective cardiovascular surgery with hemoglobin (Hb) < 12 g/dl from September 2014 to February /2016 ( n = 52) served as control group. The primary outcome was perioperative red blood cell (RBC) transfusion. Secondary outcomes were date‐of‐surgery Hb, intensive care unit (ICU) and hospital LOS, complication rates, and transfusion cost. Results: The two most common treatments were IV iron ± folate ( n = 36/45; 80%) and oral iron ( n = 9/45; 20%). As compared to historical patients, study patients had significantly higher day‐of‐surgery Hb (10.6 ± 1.4 vs. 9.8 ± 1.3 g/dl, p < .001), lower utilization of RBC transfusion (0.86 ± 1.4 vs. 2.78 ± 2.4, p < .001), fewer days in the ICU (2.1 ± 2.0 vs. 4.0 ± 3.5, p = .002), and shorter total LOS (6.9 ± 4.8 vs. 12.9 ± 6.8, p < .0001). Study patients also showed lower overall complication rates ( p < .0001). Analysis of RBC acquisition cost and transfusion cost also showed significant saving of 69% (293 vs. 945 and 656 vs. 2116, respectively). Conclusion: When corrected for type of procedures and surgeon, our pilot anemia program in elective cardiovascular surgeries showed higher day‐of‐surgery Hb and significant reduction in RBC transfusion rates, ICU and hospital LOS, and overall complication rates. Abstract : See editorial on page 2519–2521, in this issue